Kesesuain Karakteristik Pekerja dan Pekerja Pada Lingkungan Kerja Industri Mebel Ukir di Desa Petekeyan, Jepara-Jawa Tengah - Abdul Malik; Anita Kristina (MediaTrend, 2020)
This study aims to describe the work environment in the furniture industry based on the suitability of the characteristics of workers and jobs. This study used descriptive qualitative method. The study was conducted on a case that occurred at the center of the carving furniture industry in Petekeyen, Jepara-Central Java. Data collection techniques are done by interview, observation and documentation. Then the data is analyzed inductively. The results showed that the working environment in the carved furniture industry can be identified based on the suitability of the job characteristics namely the work risks faced to set safe working environment limits, the characteristics of the worker on the role of workers in his work in accordance with work procedures and work experience, and the value of the agreement norms that shape safe environmental behaviors and their interactions. The results of the study can be a material for recommendations for further research related to work environment issues that explore more deeply from the side of other phenomena that are based on cultural characteristics and safety behaviors and also on the wage mechanism so that it can know the utility value of wages and risks received.